Correction: Computational insights on the origin of enantioselectivity in reactions with diarylprolinol silyl ether catalysts via a radical pathway. Issue 15 (11th July 2022) - Lam, Ching Ching; Goodman, Jonathan M.
Abstract : Correction for 'Computational insights on the origin of enantioselectivity in reactions with diarylprolinol silyl ether catalysts via a radical pathway' by Ching Ching Lam et al., Org. Chem. Front., 2022, ; https://doi.org/10.1039/d2qo00354f .